The effect of propofol as an antioxidant agent in intravenous regional anesthesia - Erhan, O. L.; Bestas, A.; Gursu, F.; Alpay, N.; Ozer, A. B.; Gulcu, F. (Prous Science, Sa, 2006)
Intravenous regional anesthesia (IVRA) is a technique whereby a tourniquet is used to restrict blood flow to an exsanguinated limb. Propofol was shown to attenuate ischemia-reperfusion damage. We aimed to investigate the effect of low-dose propofol as an antioxidant in this process. Twenty-six unpremedicated adult patients (ASA I-II) were studied. The patients in the control group (Group C, n = 12) were administered 40 ml of 0.5% lidocaine, while the patients in the propofol group (Group P, n = 14) were administered 40 ml of 0.5% lidocaine plus 20 mg propofol for IVRA. Serum levels of malondialdehyde (MDA) and paraoxonase activity were measured at 1 min before, immediately upon, and 30 min after the release of the tourniquet. Serum paraoxonase activity was observed to have a significant decreasing course in both groups (p < 0.01). In contrast, we observed a progressive increase in the serum levels of MDA in Group C (p < 0.05). However, in Group P, serum levels of MDA after the release of the tourniquet periods were significantly lower than that before the release of the tourniquet (p < 0.05). The addition of propofol (20 mg) to lidocaine for IVRA inhibits MDA levels. We conclude that the addition of propofol to lidocaine can be considered as a useful antioxidant in this type of anesthesia. (c) 2006 Prous Science. All rights reserved.
Keywords: intravenous regional anesthesia; ischemia-reperfusion damage; malondialdehyde; paraoxonase; propofol